THE INVESTIGATION OF THE RELATIONS BETWEEN STUDENTS’ATTITUDES TOWARD THE NATURE OF TECHNOLOGY AND PROBLEMATIC INTERNET USAGE - TEKE, Aziz; SAHİN, Ismail and SADİ, Ozlem (The Eurasia Proceedings of Educational and Social Sciences, 2016)
The purpose of the present study was to explore the relevance between the sub-dimensions of the instrument for assessing students’ concepts of the nature of technology scale developed by Pey-Yan Liou and the sub-dimensions of problematic internet usage scale developed by Ceyhan, Ceyhan and Gürcan. The instrument for assessing students’ concepts of the nature of technology scale consists of six sub-dimensions named technology as artifacts, technology as an innovative change, the current role of technology in society, technology as a double-edged sword, history of technology, and technology as a science-based form. The problematic internet usage scale consists of three sub-dimensions named negative consequences of the internet, social benefit / social comfort, excessive usage. In this quantitative research survey design was used. Data in this study were collected from a total number of 365 students studying at four different high schools. In accordance with the analyses carried out in this study suggestions were made for practical and research studies.